2020
DOI: 10.1016/j.dsx.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 lockdown on patients with chronic diseases

Abstract: Background and aims We sought to measure the effect of lockdown, implemented to contain COVID-19 infection, on routine living and health of patients with chronic diseases and challenges faced by them. Methods A semi-structured online questionnaire was generated using “Google forms” and sent to the patients with chronic diseases using WhatsApp. Data were retrieved and analyzed using SPSS. Results Out of 181 participants, 98% reported effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
114
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(145 citation statements)
references
References 7 publications
4
114
0
5
Order By: Relevance
“…Studies show that patients with pre-existing, non-communicable diseases have found it difficult to maintain a healthy lifestyle 68 . Patients with coronary heart disease, diabetes, and cancer have had to compromise on their physical activity routine and dietary pattern in particular 69,70 .…”
Section: Lifestyle Of Patients With Chronic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that patients with pre-existing, non-communicable diseases have found it difficult to maintain a healthy lifestyle 68 . Patients with coronary heart disease, diabetes, and cancer have had to compromise on their physical activity routine and dietary pattern in particular 69,70 .…”
Section: Lifestyle Of Patients With Chronic Diseasesmentioning
confidence: 99%
“…In a study from France, 45% of 195 patients with chronic heart disease had >25% reduction in physical activity and 24% of patients had gained >2 kgs of weight 71 . Patients fearful of acquiring COVID-19 infection have also been found to postpone medical care for their chronic problems, leading to greater physical and psychological distress while adding to the suffering of several chronically ill patients 56,68,72 .…”
Section: Lifestyle Of Patients With Chronic Diseasesmentioning
confidence: 99%
“…2 Over the course of the COVID-19 pandemic, wound care centres have temporarily closed or restricted their hours in response to directions from the CMS and other governing bodies. 3 Wound care centres, including HBOT centres, are frequently located within hospitals that have implemented containment strategies including restrictions on visitors and the provision of outpatient services due to the COVID-19 pandemic. Unfortunately, eliminating or significantly reducing the ability to deliver quality care to wounded patients (a large proportion of whom have multiple chronic comorbid conditions such as diabetes) puts this fragile cohort at even greater risk for medical complications during the pandemic.…”
mentioning
confidence: 99%
“…As a result of the COVID-19 pandemic, patients with chronic diseases have experienced adverse health effects including missed routine medical appointments and testing. 3 In one survey of healthcare professionals worldwide, 67% of respondents reported that their patients had experienced moderate or severe effects due to COVID-19 related changes in healthcare services; diabetes was the most common condition affected by these changes. 4 The Alliance of Wound Care Stakeholders (the Alliance) is a not-for-profit organisation that promotes advocacy and outreach regarding wound care in the United States.…”
mentioning
confidence: 99%
“…18 The readiness of the Pakistan healthcare system to withstand the reemergence of COVID-19 cases is very uncertain. Lockdown measure indirectly caused the disruption of infection prevention and control programs effective in Pakistan, 19 which might cause secondary outbreaks of other infections and vaccine-preventable diseases. Amid numerous conspiracy theories, vaccine hesitancy remains a significant challenge for Pakistan.…”
mentioning
confidence: 99%